(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the linguacultural features of the concept ‘‘body’’, a comparative analysis was conducted with the concept ‘‘body’’ and two cognitive levels - meaning and internal form. Knowledge about the concepts under consideration reveals significant similarities.